Runaway Jury - Fleder, Gary, 1962-; Bruce, Davison; Bruce Mc Gill; Dustin Hoffman; Gene Hackman; Jeremy Piven; Rachel Weisz; John Cusack (USA New Regency Pictures, 2003)
Wendell Rohr is a torts lawyer taking on the gun lobby. Rankin Fitch is the jury consultant for the Defendants and between them the battle is for the hearts and minds of the jury. But there is someone on the inside. Nicholas Easter is a juror with a girlfriend, Marlee, on the outside. they have a past ..... and their own agenda.
A juror on the inside, and a woman on the outside manipulate a court trial involving a major gun manufacturer.
John Grisham
Language: English
Subtitles: English, Turkish
Keywords: Thriller; Drama